Developing a novel tool to assess the ability to self-administer medication - A systematic evaluation of patients' video recordings in the ABLYMED study - Luegering, Anneke; Langner, Robert; Wilm, Stefan; Doeppner, Thorsten R.; Hermann, Dirk M.; Frohnhofen, Helmut; Gronewold, Janine (Frontiers Media S.A., 2023)
Background: Older people often experience medication management problems due to multimorbidity, polypharmacy and medication complexity. There is often a large gap between patients' self-reported and actual abilities to handle the self -administration of their medication. Here we report on the development and evaluation of a new tool to assess the ability of non-demented hospitalized patients to self-administer medication in different dosage forms. To this end, we video-recorded the patients' medication management performance and implemented a novel assessment scheme, which was applied by several independent raters.Methods: Sixty-seven in-patients > 70 years of age and regularly taking > 5 different drugs autonomously of the ABLYMED study agreed to the video recording of their medication management performance with five different dosage forms. All raters underwent a training and applied a standardized assessment form and written guide with rating rules for evaluation. In a pilot phase, video recordings of three patients were rated by 19 raters (15 medical students, two expert raters to determine a reference standard, and two main raters who later rated the total sample). In the rating phase, based on the ratings obtained from the two main raters, we determined interrater (assessed every section of 20 patients as agreement between the raters at one point of time) and intrarater (assessed as consistency within each rater across three points of time) agreement by intraclass correlation analysis.Results: In the pilot phase we obtained an overall sufficient agreement pattern, with an adjustment of the rating rules for patches. In the rating phase we achieved satisfactory agreement between the two raters (interrater reliability) and across different points of time (intrarater reliability). For two dosage forms (eye-drops and pen), rater training needed to be repeated to reach satisfactory levels.Discussion: Our novel rating procedure was found to be objective, valid and reproducible, given appropriate training of the raters. Our findings are an important part of a larger research project to implement a novel assessment for the ability to self-administer medication in different dosage forms. Further, they can support the development of patient trainings to improve medication management and secure independent living.
Keywords: Self Administration; Aged; Medication Management Problems; Self-Reported Ability; Video Recordings; Rating Procedure